Prevalence of Type 2 Diabetes Risk in a Higher Education Community of North-Eastern Portugal: a Prospective Cross-sectional Observational Analysis - Carlos M. Duarte; Pedro Magalhães; Laissa S. Saldanha; José E. Teixeira; José Bragada (Sapientia Publishing Group, 2024)
OBJECTIVES Type 2 diabetes (T2D) is considered one of the most prevalent diseases worldwide. The aim of this study was to analyse the risk of developing T2D in a higher education community of Bragança, North-Eastern Portugal. METHODS The observational, cross-sectional and prospective sample comprised 3021 individuals, aged between 18 and 64 years old, of whom 1759 were women (mean age 24.16 ± 8.80 years) and 1263 were men (mean age 23.37 ± 8.70 years). The Finnish Diabetes Risk Score (FINDRISC) questionnaire was employed to estimate the risk of developing T2D over the next 10 years. RESULTS The results indicated that approximately 37 (1%) participants in the sample exhibited a high risk of developing T2D, 117 (4%) participants exhibited a moderate risk, 660 (22%) participants exhibited a slight risk, and 2206 (73%) participants exhibited a low risk. A higher T2D risk was observed in the staff group in comparison with the other groups (p < 0.001). Furthermore, body mass index (BMI) and waist circumference (WC) were the variables that most contributed to the increased risk of developing T2D (X2 = 1034.5; p < 0.001). CONCLUSIONS In conclusion, the study reported a low T2D risk for the higher education community of Bragança in the Portuguese North-Eastern region. However, the risk of T2D was found to be higher in the staff group than in the student group. The FINDRISK questionnaire may be applied for the early diagnosis of T2D risk factors.